2015
DOI: 10.1016/j.icarus.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the sequestration of hydrogen-bearing volatiles towards the Moon’s southern pole-facing slopes

Abstract: a b s t r a c tThe Lunar Exploration Neutron Detector (LEND) onboard the Lunar Reconnaissance Orbiter (LRO) detects a widespread suppression of the epithermal neutron leakage flux that is coincident with the pole-facing slopes (PFS) of the Moon's southern hemisphere. Suppression of the epithermal neutron flux is consistent with an interpretation of enhanced concentrations of hydrogen-bearing volatiles within the upper meter of the regolith. Localized flux suppression in PFS suggests that the reduced solar irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
(94 reference statements)
1
5
0
Order By: Relevance
“…Therefore, a subsurface layer of ice could cause a lower d/D ratio, as observed of craters containing PSRs. Furthermore, the flatter average slopes on craters containing PSRs coincide with McClanahan et al [4], who observed that craters with an average wall slope of less than 20°are more likely to bound ice on the surface. Accordingly, if a layer of ice were present in these regions, we would expect the d/D ratio and the crater topography between the populations to be as distinguishable as we observed.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, a subsurface layer of ice could cause a lower d/D ratio, as observed of craters containing PSRs. Furthermore, the flatter average slopes on craters containing PSRs coincide with McClanahan et al [4], who observed that craters with an average wall slope of less than 20°are more likely to bound ice on the surface. Accordingly, if a layer of ice were present in these regions, we would expect the d/D ratio and the crater topography between the populations to be as distinguishable as we observed.…”
Section: Discussionsupporting
confidence: 82%
“…Arnold [2] corroborated the idea of PSRs harboring volatiles, especially water ice, at the lunar south pole. Recent investigations also concur with this hypothesis (Nozette et al [3], McClanahan et al [4], and Susorney et al [5]) however, others (Eke et al [6], Haruyama et al [7]) did not find any compelling results.…”
Section: Introductionmentioning
confidence: 79%
“…Figure 14 shows the high correlation between the general trends with latitude of decreasing average illumination poleward with the reduction in neutron counts as measured by both the Lunar Prospector Neutron Spectrometer (LPNS) and the Lunar Exploration Neutron Detector (LEND) (Mazarico et al, 2011a). Further studies further established this link, and showed the importance of maximum slope and slope azimuth on the presence of subsurface volatiles (McClanahan et al, 2015). Another derived product, the so-called sky visibility that describes the sky solid angle visible from the surface, was important to correct the Lyman Alpha Mapping Project (LAMP) observations and measure the surface albedo at UV wavelengths (Gladstone et al, 2012).…”
Section: Illumination Conditions At the Lunar Polesmentioning
confidence: 85%
“…Likewise, solar wind also directly interacts with asteroids or planets in absence of an atmosphere and intrinsic magnetic field. The best-known example is the interplay between the solar wind and the Moon [14,15]. Also in the direct surroundings of the Earth, several kinds of natural plasmas exist, such as the magnetosphere, plasmasphere, ionosphere and the polar auroras.…”
Section: Plasma-surface Interaction Physics -An Overarching Domain Wh...mentioning
confidence: 99%